A new species of Polycarpaea (Caryophyllaceae) from India - Geethakumary, M. P.; Deepu, S.; A. R., Viji; Pandurangan, A. G. (Phytotaxa, 2019)
Polycarpaea rangaiahiana, a new species of Caryophyllaceae from the lateritic plains of Kannur District, Kerala, India is described and illustrated. P. rangaiahiana is morphologically similar to P. aurea from which differs in having ovate-lanceolate stipules with fimbriate margin and other floral characters. The name P. aurea is discussed from the nomenclatural point of view and a second-step typification was proposed.